Knowledge and attitudes of University of Limpopo's postgraduates students towards mental illness - Mokwebo, Jackson (My University, 2018)
Extensive research on the knowledge and attitudes of students regarding mental illness has been conducted among university students globally. Some of these studies have indicated that students’ attitudes are influenced by a number of factors such as gender, year of study and contact with people with mental illness. In addition, university students’ attitudes towards people with mental illness were found to vary based on the course that they were enrolled in. The present study sought to explore the knowledge and attitudes of university postgraduate students towards mental illness. A survey research design was adopted. Using systematic random sampling, 143 students enrolled for an honours degree in the Faculty of Humanities at the University of Limpopo were selected and enlisted to participate in the study. The students completed a self-reported questionnaire including the Mental Health Knowledge Schedule (MAKS) and Attitude Scale for Mental Illness (ASMI). The results of the study indicate that nearly half of students (49.7%) have adequate knowledge about mental illness. Most students (mean = 38.55) were able to identify mental disorders and were familiar with various treatment modalities. Gender, study course, and previous contact with people with mental illness had no effect on the students’ knowledge of mental illness. A further exploration revealed that 50.3% of the students displayed favourable attitudes towards people with mental illness. 31.5% of the students reported having previous contact with people with mental illness. A majority (60%) of students who had previous contact with someone with mental illness displayed favourable attitudes compared to students (46%) with no previous contact. Lastly, there was no relationship between the students’ knowledge about mental illnesses and their attitudes. The results suggest that educational and awareness campaigns aimed at improving students’ knowledge about mental illness and attitudes should promote contact with the mentally ill. However, the contact should be the type that will cultivate positive attitudes.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2018
Keywords: Mental illness; University students; Attitudes; Mental illness; Mental illness -- Social aspects; College students -- South Africa -- Attitudes